SUPERVISED LEARNING WORKSHOP;A NEW, INTERACTIVE APPROACH TO UNDERSTANDING SUPERVISED LEARNING ALGORITHMS, 2ND EDITION - BLAINE BATEMAN; ASHISH RANJAN JHA; BENJAMIN JOHNST (PACKT Publishing, 2020)
Cut through the noise and get real results with a step-by-step approach to understanding supervised learning algorithms.